Implementasi Sistem Keuangan Desa (SISKEUDES) dalam Meningkatkan Efektivitas Pengelolaan Keuangan Desa di Desa Telukbuyung Kabupaten Karawang - Amelda; Sihabudin; Fauzi, Robby (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Teluk Buyung Village, Karawang Regency has implemented the SISKEUDES application since 2017 as a government effort to increase the effectiveness of village financial management. SISKEUDES is a technology-based application that is integrated and can make it easier for the village government to present accountable and transparent financial reports, in practice there are still obstacles experienced by the village government. This type of research is a qualitative descriptive research. The research was conducted on May 5, 2023. Researchers conducted research for 2 months, namely May-July 2023. The subjects for this study were the Village Head, Head of Finance for Telukbuyung Village, Pakisjaya District, Karawang Regency and BPKP West Java. This research uses two sources of data, namely primary data and secondary data. The central government's efforts to increase the effectiveness of financial management in Teluk Buyung Karawang Village experienced several obstacles, especially in the lack of understanding, resources in implementing SISKEUDES. and the recording stage which was not carried out in real time Overall, the research shows that the implementation of SIKEUDES in Telukbuyung Village has several aspects that have been implemented successfully, such as good communication, transparency, and the principle of orderly budgeting. Even though there have been positive steps, there are still obstacles that need to be overcome to increase effectiveness and efficiency, there are challenges in application operation, optimal accountability, and full participation of all related parties.